Advancements in metal oxide bio‐nanocomposites for sustainable food packaging: Fabrication, applications, and future prospectives - Jayaprakash Nandhini; Michael Bellarmin; Senthil Siva Prakash; Devarajan Sowmya Sri; Elumalai Karthikeyan (Food Bioengineering)
Abstract The research on metal oxide bio‐nanocomposites for sustainable food packaging has witnessed significant advancements, offering a promising alternative to traditional food packaging materials. This review briefly describes their fabrication techniques, applications, superiority over conventional packaging, challenges, limitations, and potential trends. These new materials are derived by incorporating metal oxide nanoparticles into the biopolymers and show better properties, such as better antimicrobial properties, which are vital in food packaging. The advantages of using metal oxide bio‐nanocomposites over typical food packaging films include enhanced mechanical properties, better moisture and oxygen resistance, bacterial resistance, and light protection. These versatile materials not only serve the purpose of properly preserving the quality and possibly even the wholesomeness of packed food products, but they are also environmentally friendly. Moreover, the review presents current developments and areas of use of metal oxide bio‐nanocomposites in food packaging and it also proposes future developments to meet the modern challenge of the food industry in the development of advanced packaging technologies.